Prevalence of e-cigarette use among tobacco smokers in six states and regions of Myanmar - Ye Phyo; Ajay M.V. Kumar; Khine Wut Yee Kyaw; Kyaw Kan Kaung; Mya Lay Nwe; Thida; Tharaphi (Addictive Behaviors Reports, 2020)
Background: Emergence of electronic cigarettes (e-cigarettes) in the past decade has the potential to undermine the global tobacco control efforts and undo the successes achieved to date. There are also concerns that e-cigarettes may become a gateway for future tobacco use and its use is increasing globally. There is no published evidence on this issue from Myanmar. Hence, we aimed to assess prevalence of e-cigarette use among tobacco smokers and its associated socio-demographic factors in six states and regions of Myanmar. Methods: This was a secondary analysis of data collected as part of a programme evaluation conducted by the National Tobacco Control Programme of Myanmar in 2018, which involved sampling 100 smokers from each state/region. We used modified Poisson regression to measure associations. Results: There were 629 tobacco smokers included in the programme evaluation. Among them, 246 (39.2%, 95% CI: 24.0%–56.7%) smokers reported that they had heard of e-cigarettes and 73 (11.6%, 95% CI: 5.1%–24.3%) reported having ever used e-cigarettes. There was no e-cigarette use among female smokers. The prevalence of e-cigarette use was significantly higher among males, students, young adults aged 18–29 years, heavy smokers (greater than 20 cigarettes per day) and those who lived in the Mandalay region. Conclusion: Our study provides preliminary evidence about e-cigarette use in Myanmar and fills an important knowledge gap. One limitation was small sample size, which is reflected by wide confidence intervals around the estimate. We recommend a national survey to obtain precise and nationally representative information.